2020
DOI: 10.1021/acs.jcim.0c00450
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Model for Predicting Protein–Ligand Unbinding Kinetics through Machine Learning

Abstract: Derivation of structure–kinetics relationships can help rational design and development of new small-molecule drug candidates with desired residence times. Efforts are now being directed toward the development of efficient computational methods. Currently, there is a lack of solid, high-throughput binding kinetics prediction approaches on bigger datasets. We present a prediction method for binding kinetics based on the machine learning analysis of protein–ligand structural features, which can serve as a baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…77 A model obtained using random forest, ligand-protein interactions and information about the protein structure as descriptors achieved R 2 te of 0.43 for a test set of 28 complexes with p38 MAP kinase. 78 The study presented here had a R 2 tr higher than the method with the highest R 2 tr value, Volsurf, and R 2 te value lower than the method with the highest predictive power, the method based on SMD. On one hand, the SMD method includes more details about the ligand-protein interactions and the unbinding process.…”
Section: Discussionmentioning
confidence: 54%
“…77 A model obtained using random forest, ligand-protein interactions and information about the protein structure as descriptors achieved R 2 te of 0.43 for a test set of 28 complexes with p38 MAP kinase. 78 The study presented here had a R 2 tr higher than the method with the highest R 2 tr value, Volsurf, and R 2 te value lower than the method with the highest predictive power, the method based on SMD. On one hand, the SMD method includes more details about the ligand-protein interactions and the unbinding process.…”
Section: Discussionmentioning
confidence: 54%
“…75 A model obtained using random forest, ligand-protein interactions and information about the protein structure as descriptors achieved R 2 te of 0.43 for a test set of 28 complexes with p38 MAP kinase. 76 The study presented here had a R 2 tr higher than the method with the highest R 2 tr value, Volsurf, and R 2 te value lower than the method with the highest predictive power, the method based on SMD. On one hand, the SMD method includes more details about the ligand-protein interactions and the unbinding process.…”
Section: Discussionmentioning
confidence: 54%
“…When we were preparing this article, Fedorov et al reported a similar collection of kinetic data. 21 Their data set consisted of 501 protein–ligand complexes with experimentally measured dissociation rate constants. A comprehensive comparison of the two data sets was carried out from the aspects of the k off data distribution, protein types, ligand structural diversity, and complex structures.…”
Section: Resultsmentioning
confidence: 99%
“…Fedorov’s work demonstrated what an RF model could achieve on their data set. 21 Because our data set is the same in nature as theirs, we also trained a similar RF model 34 for computing the k off value of a given protein–ligand complex on our data set. To achieve this goal, the atom pair descriptors implemented in the RF-Score scoring function 35 were adopted here to construct the RF model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation